SOSIALISASI PERATURAN TURNAMEN FUTSAL STKIP MUHAMMADIYAH MUARA BUNGO - Titis Wulandari; Dedy Rahmat Saputra; Jhony Hendra (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
Educational sports are carried out with the aim of education through all movement activities that are directed to meet the needs and goals of education itself. Educational sports are identical with physical education activities, sports and health, which are carried out at every level of education or better known as physical education and sports. This service is carried out with the aim of knowing the assessment of the coach and match supervisor on the leadership of the referee in the futsal playoff match. The STKIP Muhammadiyah Muara Bungo Futsal Tournament activity will be held on January 31, 2021 at Dimas Futsal, Muara Bungo. Field results are obtained due to the factors that influence the success of a referee, namely internal and external factors. The more dominant influence is internal factors, psychological factors in the form of anxiety. To be able to lead the match well, the referee needs to master these psychological factors. How to manage these psychological factors can be by training the emotions of the referee to keep it under control. Understand patterns in mastering psychological factors and always practice